2006
DOI: 10.1111/j.1348-0421.2006.tb03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of spoT, relA and dksA Genes on Quinolone Tolerance in Pseudomonas aeruginosa under Nongrowing Condition

Abstract: Abstract:To assess the contribution of ppGpp in antibiotic tolerance to quinolone in Pseudomonas aeruginosa, knockout mutants of the genes involved or linked with the stringent response, such as relA, spoT and dksA, were constructed and investigated for their antibiotic susceptibility to quinolones. The survival of the dksA and spoT mutants in the presence of 8 g/ml of ofloxacin and 1 g/ml of ciprofloxacin were shown to be approximately 20-180 and 10-40 times respectively, higher than the same for the wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 30 publications
2
76
0
Order By: Relevance
“…A current theory proposed for persister formation in E. coli postulates that stochastic fluctuation in the production of toxic proteins known to block cell metabolism mediates entrance of cells into a dormant state enabling the persister cell to escape corruption of cellular functions by antibiotics (32). However, in both E. coli and P. aeruginosa a number of the genes that were identified to affect the persister phenotype encode global regulators, such as DnaK, DnaJ, DksA, histone-like protein, integration host factor (17), and PhoU (34) in E. coli or SpoT, RelA, DksA (62), and RpoS (42) in P. aeruginosa, suggesting that environmental signaling plays an important role in modulating persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A current theory proposed for persister formation in E. coli postulates that stochastic fluctuation in the production of toxic proteins known to block cell metabolism mediates entrance of cells into a dormant state enabling the persister cell to escape corruption of cellular functions by antibiotics (32). However, in both E. coli and P. aeruginosa a number of the genes that were identified to affect the persister phenotype encode global regulators, such as DnaK, DnaJ, DksA, histone-like protein, integration host factor (17), and PhoU (34) in E. coli or SpoT, RelA, DksA (62), and RpoS (42) in P. aeruginosa, suggesting that environmental signaling plays an important role in modulating persistence.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis about the underlying mechanism for persister formation is that persister cells are phenotypic variants which are not regulated per se but result from stochastic fluctuations of toxic proteins (32). However, several genes, including genes encoding the global stationary phase-related regulators SpoT, RelA, DskA, and RpoS (42,62), that appear to be involved in persistence in P. aeruginosa have been discovered (9,42,62). We undertook to investigate the formation of persister cells in P. aeruginosa cultures in a comprehensive analysis under various conditions related to cidal and static antibiotic challenge, quorum-sensing-mediated signaling, and environmental stress conditions.…”
mentioning
confidence: 99%
“…In P. aeruginosa, it was shown that spoT and dksA mutants had higher levels of ppGpp and were more tolerant toward fluoroquinolones (118). Furthermore, in P. aeruginosa, the stringent response is required for optimal catalase activity and mediates H 2 O 2 tolerance during both planktonic and biofilm growth.…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%
“…For example, both in E. coli and in P. aeruginosa, these include dksA, relA and spoT, genes associated with the stringent response (Hansen et al, 2008;Korch et al, 2003;Viducic et al, 2006). However, because of their simultaneous involvement in additional processes, their suitability as candidate drug targets remains to be determined.…”
Section: Global Regulatorsmentioning
confidence: 99%